Progressive steps in understanding and solving guava wilt - a national problem - MISRA, A.K. (Indian Phytopathology, 2017)
At the outset, I wish to convey my gratefulness to all the members of the Indian Phytopathological Society for unanimously electing me as President of this prestigious Society. I pay my tributes to all the eminent Plant Pathologists of India and past Presidents of the Indian Phytopathological Society, who have nurtured the society, brought international recognition for the society and contributed significantly for the subject. I feel humble and privileged to deliver this presidential lecture for the year 2015. I have selected a subject in which I have spent more than 20 years of my active research period i.e. guava wilt which is a ticklish problem.